Dry galloping in inclined cables: linear stability analysis. (2017) - Piccardo, Giuseppe; Zulli, Daniele; Luongo, Angelo
Abstract: In the last decade, dry galloping has been frequently observed on real stay cables also in the case of circular cross section. It is an aeroelastic phenomenon which occurs when structures or structural elements are generically placed with respect to the wind, being both incidence and yaw angles different from zero. Here, after writing down the equations which describe the static reference configuration of an inclined cable under the self-weight, the equations of motion are obtained up to third order, where the forces related to the wind are evaluated coherently with an aerodynamic model, drawn under the quasi-steady hypothesis. A Galerkin projection is carried out and the critical conditions causing Hopf bifurcation on the trivial equilibium configuration are then evaluated.